Inspiring elementary learners : nurturing the whole child in a differentiated classroom - Kryza, Kathleen; Duncan, Alicia; Stephens, S. Joy. (Thousand Oaks, Calif. : Corwin Press, 2009)
"Inspiring Elementary Learners offers step-by-step instructions for creating a learning environment that engages all students and provides creative strategies that can be easily implemented in the classroom. The authors include lesson examples and assessment rubrics across the core subject areas, showing how to cultivate a community of learners who honor themselves and each other. Based on current educational research on metacognitive strategies, learning styles, constructivist thinking, and choice theory, this handbook helps educators design lessons to foster students' intrinsic motivation, teach for deep understanding while meeting content standards, and create and implement differentiated strategies."--Back cover.
Includes bibliographical references
Keywords: Differentiated teaching staffs; Individualized instruction; Mixed ability grouping in education; Education, Elementary; Individualized instruction; Mixed ability grouping in education; Education, Elementary